2021
DOI: 10.3390/app112110113
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of City Roads Using Luojia 1-01 Nighttime Light Data

Abstract: The extraction of a road network is critical for city planning and has been widely studied in previous research using high resolution images, whereas the high cost of high-resolution remote sensing data and the complexity of its analysis also cause huge challenges for the extraction. The successful launch of a high resolution (130 m) nighttime remote sensing satellite, Luojia 1-01, provides great potential in the study of urban issues. This study attempted to extract city roads using a Luojia 1-01 nighttime li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…In addition, in road extraction experiments of Lhasa, Wuhan, and Beijing, we also found that the greater the traffic flow was, the lower the accuracy of these three methods became. This phenomenon is similar to the conclusion drawn from the research on extracting roads by LJ-1 NTL data [32].…”
Section: Discussionsupporting
confidence: 89%
“…In addition, in road extraction experiments of Lhasa, Wuhan, and Beijing, we also found that the greater the traffic flow was, the lower the accuracy of these three methods became. This phenomenon is similar to the conclusion drawn from the research on extracting roads by LJ-1 NTL data [32].…”
Section: Discussionsupporting
confidence: 89%
“…As one of the basic remote sensing satellite data, night-time light data (NTL) is an important data source for analyzing some urban interior problems (Liu et al, 2015), including population, GDP, and carbon emission, because of its advantage in reflecting urban activities via capturing the NTL brightness in the urban city (Zhao et al, 2015;Zhang et al, 2017;You et al, 2021), Additionally, it has also been shown by relevant studies that urban night-time light is also directly related to urban surface temperature, which also plays an important role in reflecting the urban heat island effect (Liu et al, 2021;Ren et al, 2022). Currently, there are three types of NTL data: DMSP/OLS (Elvidge et al, 2001;Small et al, 2013), NPP/VIIRS (Elvidge et al, 2021a;2021b), and Luojia-01 (Wang et al, 2021). NTL data are mainly used to identify urban centers and delineate urban boundaries; thresholds combined with NTL are used as the main tools, owing to their easier operation steps (Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Only a handful of studies have endeavored to employ NTL images for road extraction tasks, achieving some noteworthy results. For instance, Wang [18] harnessed Luojia 1-01 NTL imagery to extract roads in Wuhan through shape optimization and a thresholding approach, attaining a final extraction accuracy of 83.2%. However, the resolution of Luojia 1-01 NTL data is relatively low.…”
Section: Introductionmentioning
confidence: 99%